IMPORTANCE OF INTERNATIONAL FINANCIAL INSTITUTIONS IN THE ECONOMY - Supervisor: PhD Akhmadaliyeva Nikholakhon; Student: Xo’janiyozova O’g’iloy (The Conference Hub, 2025)
This thesis explores the reasons for formation for International Financial institutions and their current role in the modern economy focusing more on their impact on Uzbekistan's development.
Keywords: International financial institutions, Bretton Woods, World Bank, IMF, Uzbekistan, economic cooperation, financial stability.